Assistance in Strengthening MPASI (Complementary Foods for Breast Milk) Education for Optimizing Toddler Growth: Community Service in Lot Kala Village, Kebayakan District, Central Aceh Regency, Indonesia - Apriani, Widya; Irdayani, Irdayani; Hidayana, Hidayana; Dewi, Nova Ratna; Lisni, Lisni (HM Publisher, 2024)
Providing appropriate complementary food for breast milk (MPASI) is a crucial factor in supporting optimal growth and development of babies and toddlers. However, lack of knowledge and correct practice of providing MPASI is still a problem in various communities, including in Lot Kala Village, Kebayakan District, Central Aceh Regency, Indonesia. This Community Service aims to provide assistance in strengthening MPASI education for the mother community in the village. This study uses a participatory community service approach. Mentoring activities include counseling regarding the principles of providing appropriate MPASI, demonstrations on making homemade MPASI, as well as regular monitoring and evaluation. Data was collected through interviews, observations and questionnaires. Data analysis was carried out descriptively qualitatively and quantitatively. The results of this community service show an increase in mothers' knowledge regarding MPASI, an increase in mothers' skills in making homemade MPASI, as well as a change in the mother's attitude to become more positive towards giving homemade MPASI. Apart from that, there was an increase in the nutritional status of infants and toddlers after the intervention. Assistance in strengthening MPASI education has proven to be effective in increasing mothers' knowledge, skills and attitudes towards providing MPASI. This program is recommended for replication in other communities that have similar proble ms.